Factors Related to Unmet Need for Fertile Age Couples in Simpang Empat Village, Pekanbaru City in 2017 - Yessi Harnani; Rina Yulviana; Tengku Ummi Rakhmah (Journal of Midwifery and Nursing, 2020)
Unmet need is the proportion of women of childbearing age who are married or living together (sexually active) who do not want to have more children or who want to space their pregnancies, but do not use contraceptives. The impact of unmet need for family planning is the occurrence of unwanted pregnancies and the pregnancy is too close. The purpose of this study was to determine the factors associated with unmet need in Simpang Empat Kelurahan Pekanbaru City in 2017. This type of research is quantitative analytic with a cross sectional design. The population was 507 households with a sample of 81 people. This research was conducted in Simpang Empat Village, Pekanbaru City, conducted in September-December 2017. Data analysis used chi-square. The results of this study are that there is a relationship between age (p value = 0.000), number of children, level of education, knowledge, attitudes, partner support and social media with unmet need. Meanwhile, there was no relationship between the role of health workers and unmet need (p value = 0.930). The suggestion is for PUS to be able to increase knowledge about the right variety of contraceptive methods according to their needs. Correct information and knowledge can eliminate wrong perceptions and attitudes towards contraceptives. It is recommended that fertile age couples use social media wisely without swallowing the circulating information.